Clinical features of X linked juvenile retinoschisis associated with new mutations in the XLRS1 gene in Italian families. Issue 9 (20th August 2003) - Simonelli, F; Cennamo, G; Ziviello, C; Testa, F; de Crecchio, G; Nesti, A; Manitto, M P; Ciccodicola, A; Banfi, S; Brancato, R; Rinaldi, E
Abstract : Aims: To describe the clinical phenotype of X linked juvenile retinoschisis in eight Italian families with six different mutations in the XLRS1 gene. Methods: Complete ophthalmic examinations, electroretinography and A and B-scan standardised echography were performed in 18 affected males. The coding sequences of the XLRS1 gene were amplified by polymerase chain reaction and directly sequenced on an automated sequencer. Results: Six different XLRS1 mutations were identified; two of these mutations Ile81Asn and the Trp122Cys, have not been previously described. The affected males showed an electronegative response to the standard white scotopic stimulus and a prolonged implicit time of the 30 Hz flicker. In the families with Trp112Cys and Trp122Cys mutations we observed a more severe retinoschisis (RS) clinical picture compared with the other genotypes. Conclusion: The severe RS phenotypes associated with Trp112Cys and to Trp122Cys mutations suggest that these mutations determine a notable alteration in the function of the retinoschisin protein.